Epistemological Foundations and Methodological Structures: A Philosophical Review of Scientific Inquiry - Septariani; Ahmad Syukri; Badarussyamsi (International Journal of Education, Language, and Social Science, 2025)
Scientific inquiry serves as the primary engine for human civilization and knowledge development. However, conceptual ambiguities surrounding the boundaries of scientific structures, epistemology, and methodological principles often persist in contemporary discourse. This study aims to systematically analyze the fundamental structures, principles, and methodological frameworks of science through a philosophical lens, specifically examining the ontological, epistemological, and axiological dimensions of knowledge acquisition. Using a qualitative-descriptive library research method, this study analyzed authoritative texts, historical scientific paradigms, and methodological literatures. The findings reveal that the integrity of scientific knowledge relies on a triadic integration: a systematic empirical-rational structure, a rigorous adherence to objective epistemological methods (ranging from deductive-inductive reasoning to error-correction mechanisms), and an axiological responsibility. Furthermore, this study synthesizes Archie J. Bahm’s pluralistic scientific steps, demonstrating that scientific methods must adapt dynamically to multi-disciplinary challenges without compromising objective validity. Understanding this fundamental architecture is critical for sustaining rigorous scientific development and resisting pseudo-scientific paradigms in the modern era.